Difference sequence space (...) of fuzzy real numbers - Tripathy, Binod Chandra; Borgohain, Stuti (Mathematical Modelling and Analysis, 2008)
The difference sequence space  of fuzzy real numbers for both 1 ≤ p < 8 and 0